Psychiatrists on psychiatry : conversations with leaders - Bhugra, Dinesh (Oxford : Oxford University Press, 2023)
Capturing the compelling personal experiences and views of some of the great thought leaders in psychiatry, the insights in this book will appeal to future generations of academics, clinicians, health care professionals, as well as anyone with an appetite for a diverse array of life stories.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on September 20, 2023).
Keywords: Psychiatry; Psychiatrists -- Interviews; Health and Wellbeing; Clinical & internal medicine